The Effect of Anticholinergics for Prevention of Storage Symptoms After Prostate Photovaporization - Martin Way, David Alejandro; Barrabino Martin, Rocio; Puche Sanz, Ignacio; Vicente Prados, Francisco Javier; Cozar Olmo, Jose Manuel (Urology Journal, 2019)
Purpose: To evaluate the efficacy of oral anticholinergics as a preventive strategy of storage symptoms and urinary incontinence associated with the early postoperative period after Greenlight laser photovaporization of the prostate (PVP). To analyze potential variables related to the onset of these symptoms. Materials and methods: Retrospective study of 105 patients who underwent PVP using a 180-W Greenlight laser (XPS). Patients were divided into two groups, depending on whether they were or weren´t prescribed anticholinergics when discharged (oral solifenacin 5 mg for 1 month after surgery). Differences between both groups were analyzed according to IPSS, ICIQ-SF and OABq-SF scores at 1 and 6 months. The potentially predictive variables of the symptomatology after undergoing PVP that we analyzed included age, prostate volume, PSA, IPSS, ICIQ-SF, OABq-SF, Qmax, previous use of a permanent urinary catheter, energy used, and laser application time. Results: 58 patients in the group with anticholinergics and 47 in the group without anticholinergics were compared. No significant differences were observed between both groups in IPSS (p = .521), ICIQ-SF (p = .720) or OABq-SF (p = .851) at 1 and 6 months after surgery. Regardless of the use of anticholinergics, there was a significant score improvement between the first and second checkup in all the questionnaires: there was a significant decrease in the mean IPSS (p < .001) and the mean score of the eighth IPSS question on patient’s quality of life (p = .026), ICIQ- SF (p = .010) and OAB-q related to symptoms (p = .001) as well as a significant increase in the mean OAB-q score regarding quality of life (p = .005). None of the variables analyzed showed a significant relation to the storage-symptom rate, rate of incontinence, or ICIQ-SF and OABq-SF scores. Conclusions: The use of solifenacin 5 mg after Greenlight laser PVP is not an effective preventive treatment for storage and incontinence symptoms associated with this procedure, which seem to self-limit over time.